The biomechanical changes of load distribution with longitudinal tears of meniscal horns on knee joint: a finite element analysis - Zhang, Kaijia (J Orthop Surg Res, 2019)
BACKGROUND: Meniscal horns are important structures of meniscus, and longitudinal tears of these places could significantly change the load distribution among the knee joint. Few studies concerned the stress concentrated on bones, which may induce the osteonecrosis of subchondral bone. The goal of this study was to construct a finite element (FE) model with high fidelity of the knee joint and evaluate the biomechanical changes of load distribution of components after longitudinal tears of the horns of meniscus. METHODS: Computed tomography and magnetic resonance images were used to develop the FE model, and two different kinds of simulations, the vertical and the anterior load, mimicking the static stance and slight flexion simulations, were applied after longitudinal tears of the horns of meniscus. RESULTS: Significantly elevated peak compressive and shear stress was observed on the menisci, cartilages, and subchondral bones, and enlarged meniscus extrusion was noticed. Between all the four types of longitudinal tears investigated in this study, longitudinal tears at the posterior horn of the medial meniscus were found to be the most significant. CONCLUSIONS: These findings showed that longitudinal tears of the meniscal horns lead to increased magnitude and changed distribution of stress and indicated the important role of posterior horn of medial meniscus. This may contribute to the mechanism between meniscal tears and spontaneous subchondral bone osteonecrosis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13018-019-1255-1) contains supplementary material, which is available to authorized users.